THE EFFECT OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON PERFORMANCE THROUGH EMPLOYEE JOB SATISFACTION AT THE SECRETARIAT OFFICE SOUTH BURU DISTRICT - Samson Laurens (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the effect of leadership style and organizational culture on performance through job satisfaction. The population of this study were all employees at the Regional Secretariat Office of South Buru Regency totaling 147 employees. The sampling in this study was 35% of the population because the population exceeded 100 people, namely 51 people. The data were analyzed using path analysis. The results of the study indicate that leadership style and organizational culture have a direct effect on performance, or indirectly through job satisfaction.